Market Performance, Price Integration and Substitution: Case study of Gazipur Wholesale Fish Market, India - Gomathy V; Ananthan P.S.; Harish Kumar HV; Neha W Qureshi; Pownkumar; Saba Nabi (Journal of Indian Fisheries Association, 2022)
Marketing of fish and fish products is critical in India’s thriving fisheries sector, ensuring efficient distribution and consumer satisfaction. This study focuses on Delhi’s biggest wholesale fish market, assessing the market behavior, intermediaries, marketing efficiency, price trends of major fish species, and co-integration between shrimp and fish prices. Freshwater fish represents 60% of the total supply, driven by high demand. Wholesalers incur costs of Rs. 2.60 for Catla fish and Rs. 9.95 for pomfret, while retailers face costs of Rs. 4.40 and Rs. 3.77, respectively. Price spreads in channel I (Rs. 29 for catla and Rs. 60 for pomfret) exceed channel II (Rs. 14 for catla and Rs. 35 for pomfret). Marketing efficiency ranges from 6 to 12.8, favoring marine species over freshwater species. 31% of fish-consuming respondents prioritize fish as their primary non-vegetarian item, with 58% expressing a preference for rohu, catla, and magur species. Over 2010-2018, shrimp prices experienced marginal growth (0.5% CAGR), with shrimp-50 exhibiting significant price fluctuations due to consumer preference. Co-integration analysis reveals price integration among black pomfret, rohu, pangasius, seer fish, and shrimp-20, with seer and black pomfret acting as substitutes. Establishing a cold storage plant and a fish waste management facility is recommended to ensure an uninterrupted cold chain and expand market capacity as a central supply and consumption hub for northern India.